2018
DOI: 10.1186/s40529-018-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of rice 9-cis-epoxycarotenoid dioxygenase 4 (OsNCED4) in Arabidopsis confers sugar oversensitivity and drought tolerance

Abstract: BackgroundThe 9-cis-epoxycarotenoid dioxygenases OsNCED4 was cloned from rice in conjunction with OsNCED 1-3 and 5, of which 3 has been shown to function in ABA biosynthesis and alteration of leaf morphology. In higher plants, NCEDs have been shown to be key enzymes controlling ABA biosynthesis and belong to a differentially expressed gene family. Aside from OsNCED3, it remains largely unknown if other OsNCED genes are involved in ABA biosynthesis in rice. Thus, transgenic Arabidopsis plants overexpressing OsN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 36 publications
5
24
0
Order By: Relevance
“…Recent study has shown that overexpression of OsNCED3 or OsNCED4 in plants can enhance water stress tolerance by increasing ABA levels [25,45]. In our study, proline accumulated drastically in response to drought and salt stress in OsMADS23-overexpressing lines (Figs 3I and S5H), hinting OsMADS23 might activate the expression of proline synthetic genes such as OsP5CR or OsP5CS1 to modulate stress tolerance.…”
Section: Osmads23 Directly Activates the Transcription Of Osnceds And Osp5cr Through Binding The Carg-box Motifssupporting
confidence: 60%
“…Recent study has shown that overexpression of OsNCED3 or OsNCED4 in plants can enhance water stress tolerance by increasing ABA levels [25,45]. In our study, proline accumulated drastically in response to drought and salt stress in OsMADS23-overexpressing lines (Figs 3I and S5H), hinting OsMADS23 might activate the expression of proline synthetic genes such as OsP5CR or OsP5CS1 to modulate stress tolerance.…”
Section: Osmads23 Directly Activates the Transcription Of Osnceds And Osp5cr Through Binding The Carg-box Motifssupporting
confidence: 60%
“…ONAC066 was previously found to directly bind to the promoter of OsNCED4 to modulate its expression ( Liu et al, 2018 ). OsNCED4 is one of the 9- cis -epoxycarotenoid dioxygenases acting as a rate-limiting enzyme for abscisic acid biosynthesis ( Huang et al, 2018 , 2019 ; Hwang et al, 2018 ). Considering that ONAC066 is a transcription activator ( Figure 2 ), the binding of ONAC066 to OsNCED4 promoter should drive the expression of OsNCED4 , which in turn leads to ABA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the upregulated genes in shoots of both rice genotypes, a total of 88 genes were assigned to metabolic pathways. Among these genes, Os07g0154100 and Os08g0445700 , have been reported to be involved in responses to abiotic stress [ 39 42 ], with the former encoding 9-cis-epoxycarotenoid dioxygenase, which is a key gene in gibberellic acid biosynthesis, and the latter encoding a stress responsive gene, trehalose-6-phosphate synthase. Expression of OsNCED4 in Arabidopsis increased ABA levels and enhanced tolerance to drought and moderate salt stress [ 39 ], and transgenic rice overexpressing OsTPSs accumulated trehalose, which could confer greater tolerance to cold, high salinity, and drought stress [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, Os07g0154100 and Os08g0445700, have been reported to be involved in responses to abiotic stress [39][40][41][42], with the former encoding 9-cis-epoxycarotenoid dioxygenase, which is a key gene in gibberellic acid biosynthesis, and the latter encoding a stress responsive gene, trehalose-6-phosphate synthase. Expression of OsNCED4 in Arabidopsis increased ABA levels and enhanced tolerance to drought and moderate salt stress [39], and transgenic rice overexpressing OsTPSs accumulated trehalose, which could confer greater tolerance to cold, high salinity, and drought stress [40][41][42]. For the common upregulated genes in roots of both rice genotypes, genes were significantly enriched in metabolic pathways and betalain biosynthesis.…”
Section: Plos Onementioning
confidence: 99%